Exposure to Low Irradiances Favors the Synthesis of 9-cis β,β-Carotene in Dunaliella salina (Teod.) - Orset, Sandra Charlotte (American Society of Plant Physiologists, 2000)
We examined the effect of irradiance on the synthesis of β-carotene and its isomers by Dunaliella salina. Growth irradiance had a marked effect both on growth of the alga (which was suppressed at both low and high irradiances) and on the accumulation of β-carotene. The accumulation of β-carotene but not α-carotene was closely linked to an increase in irradiance. Growth at low irradiances (20–50 μmol m(−2) s(−1)) promoted a high ratio of 9-cis to all-trans β-carotene (>2:1), while exposure to high irradiances (200–1,250 μmol m(−2) s(−1)) resulted in a large reduction in this ratio (to <0.45:1). A similar pattern was seen for the geometric isomers of α-carotene, with exposure to low irradiance favoring the accumulation of the 9-cis form. The carotenoid biosynthesis inhibitors 4-chloro-5(methylamino)-2-(α-α-α-trifluoro-m-tolyl)-3-(sH)-pyridazinone and 2-(4-chlorophenylthio)triethylamine caused the accumulation of the precursors phytoene and lycopene, respectively, in D. salina. High-performance liquid chromatography and infrared analysis showed that phytoene adopted the 15-cis and all-trans forms (as in higher plants), and that lycopene primarily adopted the all-trans form. This indicates that isomerization of β-carotene takes place during or after cyclization.